2008
DOI: 10.1016/j.urology.2008.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Concordance of Sporadic Synchronous Bilateral Renal Masses

Abstract: These data demonstrate that in cases of bilateral sporadic localized synchronous renal masses, a diagnosis of ipsilateral renal cell carcinoma is associated with contralateral renal cell carcinoma in the vast majority of patients, whereas ipsilateral benign pathology is associated with contralateral benign disease at a substantially lower rate. Histologic concordance is similarly high, meaning most cases of clear cell or papillary tumors ipsilaterally are concordant in the contralateral kidney. Concordance rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Bilateral synchronous renal tumors have been evaluated in many studies [24]. Patel et al [17] more recently found that malignant concordance was 89% among the patients who had bilateral synchronous renal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral synchronous renal tumors have been evaluated in many studies [24]. Patel et al [17] more recently found that malignant concordance was 89% among the patients who had bilateral synchronous renal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…14 Earlier efforts to define pathological concordance rates of renal tumors focused primarily on cases of sporadic BSRMs. 6,7,16,17 In the largest report of BSRMs analyzing malignant, histological and grade concordance Rothman et al noted a rate of 99%, 93% and 83%, respectively, in a review of SEER data. 7 More recently, in a single institution retrospective account Patel et al reported similarly high rates of malignant concordance in 89% of patients who presented with BSRMs.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,16,17 In the largest report of BSRMs analyzing malignant, histological and grade concordance Rothman et al noted a rate of 99%, 93% and 83%, respectively, in a review of SEER data. 7 More recently, in a single institution retrospective account Patel et al reported similarly high rates of malignant concordance in 89% of patients who presented with BSRMs. 8 In contrast to bilateral renal masses, our examination of unilateral synchronous multifocal disease revealed a much lower malignant concordance rate of 77.2%.…”
Section: Discussionmentioning
confidence: 99%
“…19 Although some clinicians advocate the use of percutaneous biopsy in the majority of patients for risk stratification, others selectively use renal biopsy in patients with absolute or relative indications or specific circumstances where nephron preservation is paramount such as synchronous bilateral lesions. 20 …”
Section: Discussionmentioning
confidence: 99%